2011
DOI: 10.1249/01.mss.0000401845.48483.9e
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Ramadan Fasting On Repeated Sprint Ability In Young Children

Abstract: 666and time. 50 m, 100 m and 200 m individual short course best performances of the season, in the four swimming strokes, were used to compare with the ACV assessed. Pearson correlation coefficient was calculated and repeated measures t-test was applied (p≤0.05). RESULTS: ACV was correlated with the 50 m swimming event velocity in breaststroke (r=0.92), front crawl (r=0.85) and backstroke (r=0.85), and with the 100 m swimming event velocity in the same swimming strokes (breaststroke: r=0.90; front crawl: r=0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…1). This is opposite to that observed by Girard and Farooq (7) [showing that BM (kg) was elevated at R4 (46±3) and AR2 (47±3) vs. BR (45±3)] but similar to the findings of Meckel et al (6) [no significant change in BM (kg) in the last 2 days of Ramadan (63±7) when compared to BR (63±7)]. Differences in daily habits, occupation and social and geographical environment can influence the energy balance and may contribute to the inconsistency in findings among studies (summarised in Supplementary Table 1) (6).…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…1). This is opposite to that observed by Girard and Farooq (7) [showing that BM (kg) was elevated at R4 (46±3) and AR2 (47±3) vs. BR (45±3)] but similar to the findings of Meckel et al (6) [no significant change in BM (kg) in the last 2 days of Ramadan (63±7) when compared to BR (63±7)]. Differences in daily habits, occupation and social and geographical environment can influence the energy balance and may contribute to the inconsistency in findings among studies (summarised in Supplementary Table 1) (6).…”
Section: Discussioncontrasting
confidence: 98%
“…Meckel et al (6) concluded that participation in RF reduced endurance (increase in the 3,000-m running time and in the sum of 6×40 m run time) and vertical jump performance but had no significant effect on 40-m sprint performance and 4×10-m shuttle run time. Girard and Farooq (7) concluded that repeated sprinting performance (6×15-m interspersed with 15 s of passive recovery) was compromised towards R4 and that this effect persisted after Ramadan (AR2), while fatigue resistance was not affected. Aloui et al (8) concluded that RF led to impairment in soccer players’ performances in the afternoon and affected the participants’ diurnal pattern observed BR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations